The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jora.12463
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to Parents and Aggressiveness in Adopted Adolescents: A Multi‐Sample Comparison Study

Abstract: This study examined adopted adolescents' levels of attachment security to parents and aggressiveness as compared to those of community nonadopted adolescents and of clinical nonadopted adolescents. Three different subsamples participated (n = 262): 101 community nonadopted adolescents (48.5% girls), 80 community adopted teens (65.0% girls), and 81 nonadopted counterparts (35.8% girls) who participated in a treatment program for youth with behavioral problems. There were no differences between community groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…An additional new insight of our study regards the ecological validity of the present model. Previous findings have acknowledged the need of more studies examining in-depth the specific mechanisms that contribute to the promotion of the development of attachment security in adopted teens [ 57 , 88 ] and of the effect of attachment in aggressiveness [ 52 ]. In spite of adopted adolescents’ more difficult previous rearing experiences—e.g., loss, maltreatment, neglect [ 89 ]—the present study showed that the contribution of coercion/imposition and acceptance/involvement parenting practices to attachment security and aggressiveness was the same in these teens as in non-adopted counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional new insight of our study regards the ecological validity of the present model. Previous findings have acknowledged the need of more studies examining in-depth the specific mechanisms that contribute to the promotion of the development of attachment security in adopted teens [ 57 , 88 ] and of the effect of attachment in aggressiveness [ 52 ]. In spite of adopted adolescents’ more difficult previous rearing experiences—e.g., loss, maltreatment, neglect [ 89 ]—the present study showed that the contribution of coercion/imposition and acceptance/involvement parenting practices to attachment security and aggressiveness was the same in these teens as in non-adopted counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that these types of problems put them at a high risk of mental health troubles, especially externalizing-behavioral problems, in comparison to their non-adopted peers (for some reviews, see [ 50 , 51 ]). However, even though adverse experiences before adoption can make adopted adolescents more likely to develop aggression problems, only a few studies have focused on the aggressiveness domain in adopted teens specifically [ 52 ]. In any case, in spite of this increased risk, there is also relevant evidence demonstrating that many adoptees exhibited resilience [ 50 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaire-based studies suggest no difference with COM peers in levels of attachment security (Altinoglu-dikmeer et al, 2014;Barroso et al, 2018;McSherry et al, 2016;Paull, 2013;Torres-Gomez et al, 2018), except in one case (Vantieghem et al, 2017).…”
Section: Key Practitioner Messagesmentioning
confidence: 96%
“…LA adolescents receive mainly secure–autonomous classifications in most interview‐based studies (summarized in Table 1 of Muzi & Pace, 2021), but one study reports less secure classifications in them compared to COM peers (Peñarrubia et al, 2022), and they show more disorganization in another study (Pace et al, 2018). Questionnaire‐based studies suggest no difference with COM peers in levels of attachment security (Altinoglu‐dikmeer et al, 2014; Barroso et al, 2018; McSherry et al, 2016; Paull, 2013; Torres‐Gomez et al, 2018), except in one case (Vantieghem et al, 2017).…”
Section: Introductionmentioning
confidence: 99%